Analisis Penggantian Material Agregat Klas A Dan B Menjadi CTRB Paket Peningkatan Jalan Muara Teweh – Benangin Menggunakan Metode AASTHO’93 - Nasib A. Sera (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Roads are one of the infrastructures that will accelerate the growth and development of an area and open up socio-economic and cultural relations between regions. Along with the progress of infrastructure, the government has developed transportation facilities, namely the improvement of the Muara Teweh - Benangin road. In the Law of the Republic of Indonesia No.38 of 2004 concerning road infrastructure, roads have an important role in realizing the development of the nation's life. The improvement of the Muara Teweh - Benangin road used the flexible pavement thickness planning with the AASTHO 1993 method, the planned road life for flexible pavement was 20 years and the traffic growth factor was 6%. Sources of data used to plan flexible pavements were obtained from the Ministry of Public Works, Directorate General of Highways - National Executive Office VII. The data derived from the documentation is CBR data of subgrade and average traffic (LHR). These data are the basis most needed in planning a flexible pavement using the AASTHO method 1993. Based on the results of the calculation of the flexible pavement thickness planning using the AASTHO method, the following comparisons are obtained: (a) the total thickness of the surface layer HRS-Base / ATB 6 cm + HRS WC 3 cm, the upper foundation layer of class A = 15 cm, and the lower foundation layer of class B = 20 cm at a cost of Rp. 35,742,463,681, with an implementation time of 265 calendar days. (b) total surface layer thickness of HRS-Base / ATB 6 cm + HRS WC 3 cm, foundation layer CTRB 35 cm, at a cost of Rp. 34,278,182,220, - with execution time of 250 calendar days, resulting in a cost efficiency of Rp. 1,464,281,462, - with a difference of 15 calendar days